Пошаговое объяснение:
а. 0,3(8-3х)=3,2-0,8(х-7)
3х-х=-0,3-8+3,2-0,8
2х=-5,3
х=-5,3:2
х=-2,65
б. 5•(х-2)=3•(х+2)
5х-10=3х+6
5х-3х=10+6
2х=16
х=16:2
х=8
с.(10-х):2=(х+12):9
х-х
тут уже начало получается 0,значит нет решения
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Пошаговое объяснение:
а. 0,3(8-3х)=3,2-0,8(х-7)
3х-х=-0,3-8+3,2-0,8
2х=-5,3
х=-5,3:2
х=-2,65
б. 5•(х-2)=3•(х+2)
5х-10=3х+6
5х-3х=10+6
2х=16
х=16:2
х=8
с.(10-х):2=(х+12):9
х-х
тут уже начало получается 0,значит нет решения